Photolysis Reaction of Linear Alkhylbenzene Sulphonate in Saturated Soil: Kinetics Parameters Evaluation - Rahayuningsih, Edia; Bendiyasa, I Made; Radjagukguk, B (ASEAN Journal of Chemical Engineering, 2009)
Fate of detergent of linear alkhylbenzene sulphonate (LAS) in the soil can be described if the values of kinetics parameters are known. The objectives of the study were to determine the kinetics parameters of photolysis reaction of LAS in saturated soil system, to identify variables affecting the parameters, and to set-up empirical equations correlating parameter to the pertinent variables. The experimental works were performed in batch reactor which was equipped with ultraviolet of 53 or 789 lumens. One hundred grams of soil was mixed with 1000 ml of water and then the mixture was left for 24 hour in the reactor. A certain amount of LAS was then added to the soil solution and stirrer was put on, so that the LAS concentration in the mixture became 20 ppm. Before the light put on, the soil solution was analyzed its biomass content using a plate count method and LAS concentration using Methylene Blue Active Substances (MBAS) method. Subsequently the slurry were stirred and lighted continuously. At a certain time interval, 5 cubic centimeters of solution was taken from the reactor then its biomass content and LAS concentration were analyzed. The variables studied were different soil type and the light intensity. When effects of one variable studied, the other variables were kept constant. Photolysis reaction of LAS in saturated soil took place both in soil solution and particle. The kinetics parameters are the function of soil organic matter (%OM) and clay mineral (%CM) content, as well as light intensity. The photolysis reaction rate constants of LAS in soil solution and particle for light intensity of 53 lumens are described as follows: kPS = 3.79 x 10 -4 (%OM) + 4.41 x 10 -3 (%CM) kPL = 7.73 x 10 -3 (%OM) + 1.18 x 10 -3 (%CM) For the light intensity of 789 lumens, the kinetics parameters are kPS = 16.3 x 10 -4 (%OM) + 0.075 x 10 -3 (%CM) 30 Photolysis Reaction of Linear Alkhylbenzene Sulphonate in Saturated Soil: Kinetics Parameters Evaluation kPL = 49.3 x 10 -3 (%OM) + 1.46 x 10 -3 (%CM) kd = 8.06 x 10 -4 (%OM) + 7.39 x 10 -5 (%CM)